Treatment of Demodicosis with Pyoderma in Siberian Husky: A Case Study - Putu Ayu Sisyawati Putriningsih; I Gusti Made Krisna Erawan; Pandu Adjie Pamungkas (Institute for Research and Community Service, Udayana University, 2022)
A 1 year and 3 month female Siberian Husky dog with a body weight of 12.20 kg was checked with some complaints: pruritus, redness, hair loss, and scaling on the body. Physical examination showed the high intensity of pruritus on the forelimbs; erythema, alopecia on the forelimbs and hindlimbs, neck, thorax, and abdomen; scales on the cranial and caudal extremities; pustules on the medial hindlimbs; warm and swelling of the forelimbs. Direct microscopic examination using deep skin scrapings found the presence of Demodex sp. mites in large numbers in each field of view. Hematological test results revealed leukocytosis and neutrophilia. Impression smear which was followed by cytology found many neutrophil infiltrations, monocytes, and cocci bacteria inside and outside the neutrophil indicating a bacterial infection. Based on the anamnesis, physical examination, and laboratory tests, the dog was diagnosed with demodicosis accompanied by pyoderma with a fausta prognosis. The treatments given were ivermectin, amoxicillin, and topical therapy with sebazole® shampoo, diphenhydramine HCl, oclacitinib, and tolfenamic acid. Three weeks after treatments were the disappearance of pruritus and pustules, the reduction of erythema, and the growth of the hair. In addition, as laboratory confirmation, using deep skin scraping identified only 1-2 mites in each field of view.